Growth and productivity: The role of government debt - Afonso, António (2013)
We use a panel of 155 countries to assess the links between growth, productivity and government debt. Via growth equations we assess simultaneity, endogeneity, cross-section dependence, nonlinearities, and threshold effects.We find a negative effect of the debt ratio. For the OECD, the higher the debt maturity the higher the economic growth; financial crisis is detrimental for growth; fiscal consolidation promotes growth; and higher debt ratios are beneficial to TFP growth. The growth impact of a 10% increase in the debt ratio is −0.2% (0.1%) respectively for countries with debt ratios above (below) 90% (30%), and an endogenous debt ratio threshold of 59% can be derived.